운광벼 유전배경의 복합내병성 조생 벼 ‘아이에스592비비’ - 박현수(Hyun-Su Park), 백만기(Man-Kee Baek), 김우재(Woo-Jae Kim), 이창민(Chang-Min Lee), 지현소(Hyeonso Ji), 서정필(Jung-Pil Suh), 정오영(O-Young Jeong), 조영찬(Young-Chan Cho), 이점호(Jeom-Ho Lee) (Korean journal of breeding, 2020)
The cultivation of early maturing rice in the plain areas in Korea is increasingly diversifying its cropping systems. Early maturingrice cultivars are usually vulnerable to bacterial blight (BB) and rice stripe virus (RSV) compared to mid- and mid-late maturing rice cultivars. To enhance the resistance of early maturing rice against BB and RSV, ‘IS592BB’ was developed by introgression of resistance genes, Xa3,Xa21, and Stvb-i into the genetic background of ‘Unkwang’, an early maturing rice cultivar with excellent agronomic characteristics. ‘IS592BB’was derived from a backcross between ‘Unkwang’ and the F1 cross between ‘Unkwang’ and ‘SR31206-12’ (‘Unkwang’/‘SR30075’) and selectedthrough the pedigree method, yield trials, and local adaptability tests. Using bioassay and marker-assisted selection to BB and RSV, Xa3,Xa21, and Stvb-i were pyramided in ‘IS592BB’. ‘IS592BB’ exhibited high-level and broad-spectrum resistance against BB, including the K3arace, the most virulent race in Korea, and also showed a resistance reaction to RSV. ‘IS592BB’ was found to be an early maturing ricecultivar with similar agronomic characteristics to ‘Unkwang’ such as early maturing, lodging tolerance with short culm, erect plant architecture,blast resistance, and high-yielding performance. In the genetic background analysis using 771 KASP (Kompetitive Allele-Specific PCR) markers,‘IS592BB’ was confirmed to be the near-isogenic line (NIL) of ‘Unkwang’ with a 93.6% recovery rate. ‘IS592BB’ was successfully introgressedwith the Xa3+Xa21+Stvb-i genes into ‘Unkwang’ without linkage drag negatively affecting its agronomic characteristics. ‘IS592BB’ wouldenhance the adaptability of early maturing rice in the plain area through its multiple disease resistance (Registration No. 7648). KCI Citation Count: 7